2013
DOI: 10.1371/journal.pone.0064868
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Interferon-Stimulated Genes on the IL-4 Response Axis by Epstein-Barr Virus Infected Human B Cells; Relevance to Cellular Transformation

Abstract: Epstein-Barr virus (EBV) is an oncogenic virus that is associated with the pathogenesis of several human lymphoid malignancies, including Hodgkin's lymphoma. Infection of normal resting B cells with EBV results in activation to lymphoblasts that are phenotypically similar to those generated by physiological stimulation with CD40L plus IL-4. One important difference is that infection leads to the establishment of permanently growing lymphoblastoid cell lines, whereas CD40L/IL-4 blasts have finite proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…2C and D). Our results were consistent with data reported previously from the laboratory of M. Rowe (17). Our results demonstrated that anti-CD40/IL-4 can reduce expression of DUSP6, which is consistent with the findings obtained by Rowe et al using array and RT-Q-PCR analysis; furthermore, they found that only IL-4 was able to attenuate this downregulation.…”
Section: Resultssupporting
confidence: 94%
“…2C and D). Our results were consistent with data reported previously from the laboratory of M. Rowe (17). Our results demonstrated that anti-CD40/IL-4 can reduce expression of DUSP6, which is consistent with the findings obtained by Rowe et al using array and RT-Q-PCR analysis; furthermore, they found that only IL-4 was able to attenuate this downregulation.…”
Section: Resultssupporting
confidence: 94%
“…We recalculated fold changes for AD and PD, and results are comparable with previous studies 18,19 . Based on the filtering criteria described in the Methods section, six datasets were selected (Table 1): GSE636063 (132 whole blood samples from healthy vs 135 AD patients 18 ), GSE99039 (whole blood samples from 232 healthy vs 204 PD patients 19 ), GSE81246 (peripheral blood mononuclear cells (PBMC) from 24 patients with latent CMV infection vs 10 patients with active disease 20 ), GSE20200 21 and GSE45829 22 (7 B cell independent samples vs 7 EBV infected samples), and GSE40396 (22 whole blood samples from seronegative patients vs 10 patients seropositive for HHV6 with fever 23 ). Table S1 summarizes all retrieved datasets along with the reasons for their inclusion or exclusion from our analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Further, among the 80 differentially expressed genes we detect, many of them represent classic host genes whose expression is modulated by EBV. Genes whose expression is concordantly activated by EBV include CD44 78 , TNFAIP2 79 , MX1 80 , and IFI44 81 ; genes with lowered expression include VAV3 82 and CD99 83 .…”
Section: Methodsmentioning
confidence: 99%